Social contract and the future of work: inequality, income security, labour relations and social dialogue (Geneva, 2016)
"This note discusses the role of the social contract between the state and other actors in defining mutual expectations for distributing power and resources to achieve social justice, the erosion of that contract as result of rising inequality and other developments in the world of work, as well as policy challenges in renewing the social contract."